Lean methodology: contributions to improving work processes in health and nursing. - Moreno Brancalion, Fernanda Novaes; Gonçalves de Souza, Lara; Berger, Simone; Costa Lima, Antônio Fernandes (Revista Brasileira de Enfermagem, 2024)
Objective: to investigate the contributions of applying the Lean methodology to improve work processes in health and nursing and its impact on associated financial aspects. Method: an integrative review, carried out in six databases, whose sample of ten (100.0%) studies was analyzed and summarized descriptively. Results: the outcomes obtained were stratified into: benefits/barriers to Lean Healthcare implementation; economic aspects involving Lean Healthcare implementation; and process improvements through Lean Healthcare implementation. The majority of studies (60.0%) were carried out in university hospitals, contexts that need to continually improve the quality of services provided, generally with scarce and limited resources, which support the viability of maintaining the teaching, research and extension tripod. Conclusion: three (30.0%) studies highlighted the financial aspects associated with Lean methodology application. The others only mentioned the possibility of financial gains through improving processes and reducing waste.